Pengaruh Integrated Marketing Communication terhadap Brand Image Glad2glow - Salsabila, Salsabila; Maulya, Widya; Q, Hawa Arofah; Hamidah, Nur; El Adawiyah, Sadiyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to provide an explanation of Integrated Marketing Communication (IMC) and Glad2glow's brand image. This study was conducted with a quantitative approach and using an online survey method. 38 people surveyed purchased and knew Glad2glow products. To show the role of IMC in creating a positive brand image and increasing consumer loyalty, data analysis was conducted using a simple linear regression test with the help of SPSS. To develop a more integrated and efficient marketing strategy, Glad2glow can consider the suggestions given.